2012
DOI: 10.1517/14740338.2012.696608
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of aliskiren in the treatment of hypertension: a systematic overview

Abstract: Aliskiren is suitable for once-daily administration. Its antihypertensive effect is comparable or superior to that of other antihypertensive agents at recommended doses. The tolerability profile of aliskiren is placebo-like at the licensed doses of 150 and 300 mg. In particular, the discontinuation of therapy due to clinical adverse events occurs similarly among patients treated with either aliskiren or placebo. Aliskiren is not recommended in association with ACE-inhibitors or angiotensin II receptor blockers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Currently the efficacy and safety of aliskiren is best tested in two clinical trials in heart failure, namely, the Aliskiren Trial of Minimizing OutcomeS for Patients with HEart failure (ATMOSPHERE) [28] and the Aliskiren Trial on Acute Heart Failure Outcomes (ASTRONAUT) [29]. However, on 20 December 2011, the Aliskiren Trial In Type 2 Diabetes Using Cardio-Renal Disease Endpoints (ALTITUDE) [30], was stopped on the recommendation after the second interim efficacy analysis [31], [32]. In this study, aliskiren or placebo was randomly assigned as an adjunct to an ACE inhibitor or ARB to type 2 diabetic patients who are at high risk for cardiovascular and renal events.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the efficacy and safety of aliskiren is best tested in two clinical trials in heart failure, namely, the Aliskiren Trial of Minimizing OutcomeS for Patients with HEart failure (ATMOSPHERE) [28] and the Aliskiren Trial on Acute Heart Failure Outcomes (ASTRONAUT) [29]. However, on 20 December 2011, the Aliskiren Trial In Type 2 Diabetes Using Cardio-Renal Disease Endpoints (ALTITUDE) [30], was stopped on the recommendation after the second interim efficacy analysis [31], [32]. In this study, aliskiren or placebo was randomly assigned as an adjunct to an ACE inhibitor or ARB to type 2 diabetic patients who are at high risk for cardiovascular and renal events.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen the development of the nonpeptide, orally long-term effective direct renin inhibitor (DRI), aliskiren, which may block the initial stages of the RAS and exert a sustained antihypertensive action in hypertensive subjects [7476]. …”
Section: Role Of Renin-angiotensin System In the Regulation Of Normentioning
confidence: 99%
“…The drug is approved for the treatment of hypertension. Recent clinical trials have shown that the addition of aliskiren to standard therapy with RAS blockade in patients with type 2 diabetes leads to more adverse events [16][17]. However, there have been no controlled studies comparing the therapeutic effects of aliskiren with ARB for the treatment of diabetes targeting the optimal blood pressure level.…”
Section: Introductionmentioning
confidence: 99%